'I eat to not die': Diet and exercise experiences of older adults living alone. (18th December 2022) - Choi, MoonKi; Bae, Juyeon
Abstract: Introduction: Living alone is a critical health risk factor among older adults. Regular exercise and a balanced diet are important for maintaining an independent and healthy life. However, it can be more difficult for older adults living alone to maintain healthy exercise and dietary habits due to their lack of social support. This study aimed to explore the life changes that accompany living alone and their needs, focussing on exercise and diet. Methods: This was a qualitative descriptive study. Purposeful sampling was conducted to recruit community‐dwelling older adults living alone. Thematic analyses were applied to analyse the qualitative data collected from semistructured interviews. Results: Fifteen subjects, including 5 men and 10 women, participated in the interviews. The median age was 77 years, ranging from 66 to 88, and the median duration of living alone was 16 years, ranging from 3 to 35. Six main themes were developed, namely unavoidable difficulties of living alone: lack of someone to depend on and loneliness, just eating 'to not die', exercise that is good for health but hard to do consistently, conflict between maintaining independence and dependence on others, coping with available resources, and resources needed for regular exercise and a balanced diet. Conclusion: Living alone leads to poor dietary habits, such as skipping meals or insufficient food intake. Food security should be ensured through the reinforcement of social support, financial assistance and the operation of public cafeterias. In addition, an individually tailored group exercise programme that can meet the need for social interaction and improve self‐efficacy would help older adults living alone maintain regular exercise habits.